The age of responsibility : CSR 2.0 and the new DNA of business. - Visser, Wayne, ....- (Chichester : Wiley, 2011)
In this landmark book Wayne Visser shows how the old model of Corporate Sustainability & Responsibility (CSR) is being replaced by a 2nd generation movement. This generation goes beyond the outmoded approach of CSR as philanthropy or public relations (widely criticised as 'greenwash') to a more interactive, stakeholder-driven model. > Provides a 'second generation' approach to CSR that will breathe new life into the movement > Can increase the effectiveness of CSR as a strategy to create positive change in society through business > Acknowledges the challenges faced by conventional businesses and provides the measures needed to face these.
Keywords: Ethisch ondernemen